Biting midges, no-see-ums Culicoides spp. (Insecta: Diptera: Ceratopogonidae): EENY349/IN626, 4/2013 - Connelly, Cynthia Roxanne (EDIS, 2013)
Biting midges can be a nuisance to campers, fishermen, hunters, hikers, gardeners, and others who spend time outdoors during early morning and evenings, and even during the daytime on cloudy days when winds are calm. They will readily bite humans; the bites are irritating, painful, and can cause long-lasting painful lesions for some people. A common observation upon experiencing a bite from this insect is that something is biting, but the person suffering cannot see what it is. This 4-page fact sheet was written by C. Roxanne Connelly and published by the UF Department of Entomology and Nematology, April 2013. http://edis.ifas.ufl.edu/in626